Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1002/macp.1988.021890402
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of soluble poly(divinylbenzene‐co‐styrene) and poly(divinylbenzene‐co‐vinylpyridine) by lithium amide‐initiated anionic copolymerization

Abstract: Polymerization of 1,4-(or 1,3-)divinylbenzene (DVB) in the presence of styrene initiated with lithium diisopropylamide was found to give soluble poly(DVB-co-styrene) having reactive vinyl group as pendant group of the polymer chain. The reactivity of 1 ,CDVB is higher than that of 1,3-DVB in the copolymerization reaction with styrene as comonomer. It was found also that 1 ,CDVB can be copolymerized with 2-vinylpyridine to form a soluble copolymer which consists primarily of 2-vinylpyridine units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In 1978, Tsuruta et al reported a particular and exceptional case where soluble polymers were obtained in high yields (∼90%) by the anionic polymerization of 1 with lithium diisopropylamide in the presence of an excess of diisopropylamine. This is probably due to the stabilization of the propagating chain-end anion by weak interaction with excess amines and the stabilized chain-end anion may possibly add to the pendant vinyl group much more slowly than the vinyl polymerization of 1 . However, the resulting polymers were observed to possess broad multimodal molecular weight distributions, indicating that they were highly branched in structure.…”
Section: Introductionmentioning
confidence: 99%
“…In 1978, Tsuruta et al reported a particular and exceptional case where soluble polymers were obtained in high yields (∼90%) by the anionic polymerization of 1 with lithium diisopropylamide in the presence of an excess of diisopropylamine. This is probably due to the stabilization of the propagating chain-end anion by weak interaction with excess amines and the stabilized chain-end anion may possibly add to the pendant vinyl group much more slowly than the vinyl polymerization of 1 . However, the resulting polymers were observed to possess broad multimodal molecular weight distributions, indicating that they were highly branched in structure.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, soluble polymers were obtained in the anionic polymerizations of 1,3-and 1,4-divinylbenzenes with use of lithium diisopropylamide in the presence of diisopropylamine. [10] This polymerization was however not a living system. In contrast to these results, the anionic polymerization of isopropenylbenzenes can be controlled to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…A particular case was reported by Tsuruta, Nagasaki, and their co-workers where soluble polymers were obtained in high yields (∼90%) by the anionic polymerization of 1 with lithium diisopropylamide with an excess of diisopropylamine. The authors suggested that the excess diisopropylamine would play an important role in stabilizing the chain-end carbanion enough to become inactive toward the pendant double bond. However, termination reactions between the excess diisopropylamine and the chain-end anion often occurred during polymerization and, therefore, this system was far from living polymerization.…”
mentioning
confidence: 99%